SMART (Smart mathematic with augmented reality technology) application for preschool - Kartika Idayu, Tajul Arifin (2019)
The focus of this project is on Augmented Reality. This study is about the development of early mathematics education applications for preschool children by using the Augmented Reality technology approach. 2D illustrated books used by teachers in the classroom or parents at home as a medium of early mathematic learning for preschoolers are getting boring and not following the latest technology developments. The traditional 2D picture book is now more attractive with the existence of augmented reality technology which is capable to bring 3D objects on the 2D image. In addition, the delivery of learning content can also be delivered more easily without the adult full guidance. In line with current phenomenon where children prefer to use gadgets instead of books, this application combines both elements which is book and gadget to enhance the interactive and fun levels among preschoolers to explore the contents of pre-school math learning. The development of SMART (Preschool Early Mathematic) is based on the Preschool Standard Curriculum (KSPK) and has been developed using the ADDIE model method. Through this application, early math learning whether at preschool or home is certainly more fun. With the existence of this application, it is hoped that it can help to increase the mastery of numerical concepts and math skills among preschoolers.